Cadmium exposure in adults across Europe: Results from the HBM4EU Aligned Studies survey 2014-2020 - Snoj Tratnik, Janja; Kocman, David; Horvat, Milena; Andersson, Anna-Maria; Juul, Anders; Jacobsen, Eva; Ólafsdóttir, Kristin; Klanova, Jana; Andryskova, Lenka; Janasik, Beata; Wasowicz, Wojciech; Janev Holcer, Natasa; et al. (International journal of hygiene and environmental health, 2022)
The objectives of the study were to estimate the current exposure to cadmium (Cd) in Europe, potential differences between the countries and geographic regions, determinants of exposure and to derive European exposure levels. The basis for this work was provided by the European Human Biomonitoring Initiative (HBM4EU) which established a framework for alignment of national or regional HBM studies. For the purpose of Cd exposure assessment, studies from 9 European countries (Iceland, Denmark, Poland, Czech Republic, Croatia, Portugal, Germany, France, Luxembourg) were included and urine of 20-39 years old adults sampled in the years 2014-2021 (n = 2510). The measurements in urine were quality assured by the HBM4EU quality assurance/quality control scheme, study participants' questionnaire data were post-harmonized. Spatially resolved external data, namely Cd concentrations in soil, agricultural areas, phosphate fertilizer application, traffic density and point source Cd release were collected for the respective statistical territorial unit (NUTS). There were no distinct geographic patterns observed in Cd levels in urine, although the data revealed some differences between the specific study sites. The levels of exposure were otherwise similar between two time periods within the last decade (DEMOCOPHES - 2011-2012 vs. HBM4EU Aligned Studies, 2014-2020). The age-dependent alert values for Cd in urine were exceeded by 16% of the study participants. Exceedances in the different studies and locations ranged from 1.4% up to 42%. The studies with largest extent of exceedance were from France and Poland. Association analysis with individual food consumption data available from participants' questionnaires showed an important contribution of vegetarian diet to the overall exposure, with 35% higher levels in vegetarians as opposed to non-vegetarians. For comparison, increase in Cd levels due to smoking was 25%. Using NUTS2-level external data, positive associations between HBM data and percentage of cropland and consumption of Cd-containing mineral phosphate fertilizer were revealed, which indicates a significant contribution of mineral phosphate fertilizers to human Cd exposure through diet. In addition to diet, traffic and point source release were identified as significant sources of exposure in the study population. The findings of the study support the recommendation by EFSA to reduce Cd exposure as also the estimated mean dietary exposure of adults in the EU is close or slightly exceeding the tolerable weekly intake. It also indicates that regulations are not protecting the population sufficiently.
Keywords: průmyslová hnojiva; monitorování životního prostředí; HBM4EU; NUTS; Europe; Evropa; průzkumy a dotazníky; Environmental Monitoring; Adult; mladý dospělý; Human biomonitoring; Phosphate fertilizer; Cadmium; Young Adult; Humans; Fertilizers; Surveys and Questionnaires; European exposure levels; kadmium; Phosphates; Industrial release; dospělí; fosfáty; lidé